2010
DOI: 10.1007/s13213-010-0070-z
|View full text |Cite
|
Sign up to set email alerts
|

Histamine in Australian wines—a survey between 1982 and 2009

Abstract: Biogenic amines are found in a range of fermented foods and beverages, including wine. Absorption of these compounds in elevated concentrations may induce headaches, gastro-intestinal and respiratory distress. The main biogenic amines found in wine are histamine, tyramine, cadaverine and putrescine. Even though concentrations of histamine in wine are generally ten-fold lower than found in some fresh and other fermented foods, their presence may contribute to an adverse reaction when consumed in combination wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…An additional potential benefit of using L. plantarum strains for MLF is that they have the ability to degrade biogenic amines (Capozzi et al 2010, García-Ruiz et al 2011), many of which have negative health implications (Bartowsky and Stockley 2011).…”
Section: Bartowsky Et Al Emerging Trends In Mlf 665mentioning
confidence: 99%
“…An additional potential benefit of using L. plantarum strains for MLF is that they have the ability to degrade biogenic amines (Capozzi et al 2010, García-Ruiz et al 2011), many of which have negative health implications (Bartowsky and Stockley 2011).…”
Section: Bartowsky Et Al Emerging Trends In Mlf 665mentioning
confidence: 99%
“…). These amounts are far in excess of those observed in wine, for example the mean histamine concentration of Australian red and white wines surveyed from 2003 to 2009 was 1.75 and 0.59 mg/L, respectively (Bartowsky and Stockley ). Indeed, the amount of histamine observed in wine is generally tenfold less than that measured in other foodstuffs associated with physiological responses (Malone and Metcalfe , Peña‐Gallego et al.…”
Section: Adverse Food Reactionsmentioning
confidence: 90%
“…Indeed, the amount of histamine observed in wine is generally tenfold less than that measured in other foodstuffs associated with physiological responses (Malone and Metcalfe , Peña‐Gallego et al. , Bartowsky and Stockley ). Furthermore, a double‐blind, placebo‐controlled study showed that there was no correlation between the histamine concentration of wine and adverse food reactions (Kanny et al.…”
Section: Adverse Food Reactionsmentioning
confidence: 92%
See 1 more Smart Citation
“…Diversos autores que han evaluado AB en diferentes tipos de vinos (tintos, blancos y rosados) han coincidido que la mayor cantidad de aminas se encuentra presente en los vinos tintos (Zee et al 1983;Lehtonen 1996;Vázquez Lasa et al 1998;Leitão et al 2005;Bartowsky & Stockley 2010;Martuscelli et al 2013).…”
Section: Factores Enológicos Que Afectan La Presencia De Aminas Biógenasunclassified